COLLABORATIVE GOVERNANCE REDUCING STUNTING IN BANDUNG CITY - Nunung Hastika; Tia Devianty; Abdul Mutolib; Tati Sarihati (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This research examines the implementation of Collaborative Governance in reducing stunting in Bandung City, Indonesia. Despite various governmental efforts to address stunting, including the national target of reducing stunting prevalence to 14% by 2024, Bandung City’s stunting rate remains high at 16.3%. Collaborative Governance, involving the participation of various stakeholders such as government agencies, the private sector, NGOs, and communities, is seen as a critical strategy for addressing this complex issue. This research uses a descriptive qualitative method to explore the factors that facilitate or hinder the implementation of Collaborative Governance in reducing stunting in Bandung. Key stakeholders in this collaboration include, Government, community leaders, NGOs, and educational institutions. The research framework is based on the model proposed by Ansell and Gash (2017), which highlights the importance of institutional design, leadership, transparency, trust-building, and effective stakeholder participation in successful Collaborative Governance. The findings reveal several challenges in the current collaborative efforts in Bandung. These include inadequate coordination between stakeholders, limited resources and infrastructure at the local level, and persistent societal stigmas that downplay the severity of stunting as a health issue. Additionally, the lack of proper training and resources for community health workers, such as those working in Posyandu), further exacerbates the problem. Moreover, the study identifies the importance of clear institutional frameworks and leadership in fostering collaboration and ensuring that all actors remain committed to the common goal of reducing stunting.